2013
DOI: 10.1007/s00296-013-2793-1
|View full text |Cite
|
Sign up to set email alerts
|

Relation of the Fas and FasL gene polymorphisms with susceptibility to and severity of rheumatoid arthritis

Abstract: To investigate associations of the Fas and FasL genes polymorphisms with rheumatoid arthritis (RA). One hundred patients with RA and age-, sex- and ethnically matched 101 controls were included. Four polymorphisms of Fas (-670 A>G rs1800682, -1377 G>A rs2234767) and FasL (IVS2nt-124 A>G rs5030772, -844 T>C rs763110) genes were typed from genomic DNA. Genotype distributions and allelic frequencies were compared between patients and control subjects. After the history and clinical examination of patients with RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Moreover, a defect in B-cell selection occurs in patients with ALPS, which is caused by impaired class-switch recombination and somatic hypermutation of the genes encoding immunoglobulins (100). Polymorphisms in the genes encoding Fas and FasL are associated with the susceptibility and severity of autoimmune lesions in patients with RA (101, 102) as well as in patients with primary SS (103). …”
Section: The Fas/fasl System In Autoimmunitymentioning
confidence: 99%
“…Moreover, a defect in B-cell selection occurs in patients with ALPS, which is caused by impaired class-switch recombination and somatic hypermutation of the genes encoding immunoglobulins (100). Polymorphisms in the genes encoding Fas and FasL are associated with the susceptibility and severity of autoimmune lesions in patients with RA (101, 102) as well as in patients with primary SS (103). …”
Section: The Fas/fasl System In Autoimmunitymentioning
confidence: 99%
“…We also noted that the overall ORs significantly changed when we deleted Zhu et al (published in 2011) [ 24 ] in homozygote model (GG vs. AA, OR = 0.843, 95% CI: 0.647–1.098, P = 0.204) and Zhu et al (published in 2016) [ 31 ] in homozygote model (GG vs. AA, OR = 0.755, 95% CI: 0.550–1.037, P = 0.082) for Fas (rs2234767) site. We found that the pooled ORs significantly differed when we deleted Sun et al 19] in dominant model (GG + GA vs. AA, OR = 0.760, 95%CI: 0.560–1.031, P = 0.078) and Seyfi et al [ 30 ] in dominant model (GG + GA vs. AA, OR = 0.679, 95% CI: 0.459–1.005, P = 0.053) for FasL (rs763110) site as well. However, there was no change in the significance of results in any models for FasL (rs5030772) site.…”
Section: Resultsmentioning
confidence: 67%
“…What’s more, the genotype distributions of controls in all of models were in accordance with HWE, except Sezgin et al [ 22 ] in Fas (rs2234767) and Seyfi et al [ 30 ] in FasL (rs5030772). However, the association was not significant change when ruled out these two studies by excluding one at a time.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…A functional study revealed that FasL rs763110−844 C allele could increase its basal expression, suggesting that this polymorphism may affect the FasL‐mediated apoptotic signaling. The FasL rs5030772 (−124 A>G, IVS2nt) polymorphism in intron 2 was associated with breast cancer, 107 RA 108 or clinical parameters in HIV‐positive patients; 109 its functional relevance has, however, not been studied. To understand the dual mechanism of Fas/FasL‐mediated apoptosis in vivo , studies on mutations in genes encoding Fas and FasL are being performed in humans and mice (homozygous for the FasL gld mutation) 110 …”
Section: Host Genetic Profile: Variability In Genes Encoding Fas Fasmentioning
confidence: 99%